Pengaruh Konsentrasi Gas Karbondioksida dan Lama Penyimpanan terhadap beberapa Aspek Viabilitas Benih Lamtoro - Rizal Kazman; Ign. Kismono; Soedarmadi . (Buletin Ilmu Makanan Ternak, 1986)
the experiment was conducted in the laboratory of agrostology, departement of animal nutrition, Bogor Agricultural University.The aim of the experiment was to study the effects of different concentration of CO2 namely 0, 40, 60, and 80%, and length of storing period namely 0, 30, 60, 90, and 120 days, on the viability of Leucaena (Leucaena leucoce phala (1am) de wit) seed. The results of the study showed that increasing concentration of CO2 up to 40% significantly increased germination and live seed persentage and maintained the water content constantly. Storing period up to 120 days decrease hard seed and increase live seed.there is no interaction between CO2 concentration and storing period.